Finding Theory–Method Fit: A Comparison of Three Qualitative Approaches to Theory Building. (July 2018) - Gehman, Joel; Glaser, Vern L.; Eisenhardt, Kathleen M.; Gioia, Denny; Langley, Ann; Corley, Kevin G.
This article, together with a companion video, provides a synthesized summary of a Showcase Symposium held at the 2016 Academy of Management Annual Meeting in which prominent scholars—Denny Gioia, Kathy Eisenhardt, Ann Langley, and Kevin Corley—discussed different approaches to theory building with qualitative research. Our goal for the symposium was to increase management scholars' sensitivity to the importance of theory–method "fit" in qualitative research. We have integrated the panelists' prepared remarks and interactive discussion into three sections: an introduction by each scholar, who articulates her or his own approach to qualitative research; their personal reflections on the similarities and differences between approaches to qualitative research; and answers to general questions posed by the audience during the symposium. We conclude by summarizing insights gleaned from the symposium about important distinctions among these three qualitative research approaches and their appropriate usages.